2010
DOI: 10.1128/mcb.01614-09
|View full text |Cite|
|
Sign up to set email alerts
|

Human Mitochondrial Leucyl-tRNA Synthetase Corrects Mitochondrial Dysfunctions Due to the tRNALeu(UUR) A3243G Mutation, Associated with Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-Like Symptoms and Diabetes

Abstract: Mutations in mitochondrial tRNA genes are associated with a wide spectrum of human diseases. In particular, the tRNA Leu(UUR) A3243G mutation causes mitochondrial encephalomyopathy, lactic acidosis, and stroke-like symptoms (MELAS) and 2% of cases of type 2 diabetes. The primary defect in this mutation was an inefficient aminoacylation of the tRNA Leu(UUR) . In the present study, we have investigated the molecular mechanism of the A3243G mutation and whether the overexpression of human mitochondrial leucyl-tRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 54 publications
(99 reference statements)
2
103
1
1
Order By: Relevance
“…Decreased mt-tRNAs levels secondary to defects in a mt-tRNA's cognate ARS2, have been observed in several other ARS2-related diseases [13,46]. Intriguingly, recent studies have shown that overexpression of cognate and non-cognate ARS2 can rescue mitochondrial dysfunction secondary to mt-tRNA mutations [47,48], further reinforcing the importance of the interaction between ARS2 and their cognate mt-tRNAs. The absence of hearing deficit in the family studied by Vanlander and co-authors, while the two families described in our study exhibit hearing loss, is an additional example of the pleiotropism of ARS2 associated disease.…”
Section: Discussionmentioning
confidence: 88%
“…Decreased mt-tRNAs levels secondary to defects in a mt-tRNA's cognate ARS2, have been observed in several other ARS2-related diseases [13,46]. Intriguingly, recent studies have shown that overexpression of cognate and non-cognate ARS2 can rescue mitochondrial dysfunction secondary to mt-tRNA mutations [47,48], further reinforcing the importance of the interaction between ARS2 and their cognate mt-tRNAs. The absence of hearing deficit in the family studied by Vanlander and co-authors, while the two families described in our study exhibit hearing loss, is an additional example of the pleiotropism of ARS2 associated disease.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, the rates of oxygen consumption in suppressed cells were directly proportional to the levels of leucyl-tRNA synthetase in A3243G mutant cells and could even reach wild-type respiratory function. The suppressed cells had increased steady-state levels of tRNA (Leu(UUR)) and up to threefold higher steady-state levels of mitochondrial translation products, but rates of protein synthesis did not differed from those in parental mutant cells [Li and Guan, 2010;Park et al, 2008].…”
Section: Increasing Mitochondrial Trna Stabilitymentioning
confidence: 92%
“…Overexpression of human mitochondrial valyl-or leucyl-tRNA synthetases increased, respectively, the steady-state levels of mutant mt-tRNA Val [71] or mt-tRNA Leu(UUR) [72], consistent with increased stability of the charged mt-tRNA. Also, overexpression of mitochondrial leucyl-tRNA synthetase rescued mitochondrial translation and respiration in cells carrying the A3243G MELAS mutation in mt-tRNA Leu(UUR) [73]. A related strategy consists in the allotopic expression of recombinant and importable tRNAs with altered aminoacylation identity.…”
Section: Gene Therapy To Reduce or Compensate For Mutant Mtdnamentioning
confidence: 99%